First data on cholesterol metabolism in Ornithodoros argasid ticks: Molecular and functional characterization of the N-terminal domain of Niemann-Pick C1 proteins - Lucía de Dios-Blázquez; Ana Laura Cano-Argüelles; Ricardo Pérez-Sánchez; María González-Sánchez; Ana Oleaga (Ticks and Tick-Borne Diseases)
Cholesterol is a molecule vital for tick physiology, but ticks cannot synthesize it and rely on dietary cholesterol. Therefore, tick proteins involved in cholesterol absorption and transport, such as the Niemann-Pick type C1 domain-containing (NPC1) proteins, are promising targets for anti-tick vaccine development. The aim of this study was to assess the structure, function, and protective efficacy of the NPC1 orthologues identified previously in the midgut transcriptomes of argasid ticks Ornithodoros erraticus and Ornithodoros moubata. For this purpose, their corresponding cDNA coding sequences were cloned and sequenced, their secondary and 3D structures were predicted, and their function was evaluated through RNAi-mediated gene knockdown and in vitro feeding on blood supplemented with ezetimibe, which inhibits cholesterol binding by NPC1 proteins. Subsequently, the protective efficacy of a recombinant form of NPC1 from O. moubata (rOmNPC1) was tested in a rabbit vaccine trial. While inhibiting cholesterol absorption with ezetimibe resulted in up to 77 % mortality in adult O. moubata, NPC1 gene knockdown and vaccination with rOmNPC1 decreased female reproductive performance in terms of the number and fertility of laid eggs. This study presents the initial molecular and functional insights into NPC1 proteins in soft ticks and supports the hypothesis that disrupting cholesterol metabolism diminishes tick viability and reproduction, rendering Niemann-Pick type C1 domain-containing proteins promising targets for drugs or vaccines.